2007
DOI: 10.1136/ard.2006.062497
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with TNF blockers and mortality risk in patients with rheumatoid arthritis

Abstract: Objective: To assess mortality in patients with rheumatoid arthritis (RA) treated with tumour necrosis factor (TNF) inhibitors, compared with a standard RA population. Methods: Patients were recruited from a regional register, which includes over 90% of patients with RA treated with TNF blockers in the area in 1999 or later, and a local community-based cohort of patients with RA, established in 1997. Of a total of 1430 patients in the combined cohort ,80 years old, 921 received treatment with TNF inhibitors du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
5
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(138 citation statements)
references
References 30 publications
7
120
5
6
Order By: Relevance
“…16 However, large, long-term international bDMARD cohorts have published early data on the relationship between TNF-a treatment and mortality. 17,18 The South Swedish Arthritis Treatment Group (established in 1999) registry and the British Society for Rheumatology Biologics Register (BSRBR, established in 2001) examined whether TNF-a inhibitor treatment was associated with increased mortality compared with patients on conventional DMARD. The Swedish group found that after adjusting for functional disability and comorbidity, treatment with TNF-a inhibitors versus those not treated was associated with a reduced mortality (hazard ratio for death was 0.65 (95% CI 0.46, 0.93)).…”
Section: Discussionmentioning
confidence: 99%
“…16 However, large, long-term international bDMARD cohorts have published early data on the relationship between TNF-a treatment and mortality. 17,18 The South Swedish Arthritis Treatment Group (established in 1999) registry and the British Society for Rheumatology Biologics Register (BSRBR, established in 2001) examined whether TNF-a inhibitor treatment was associated with increased mortality compared with patients on conventional DMARD. The Swedish group found that after adjusting for functional disability and comorbidity, treatment with TNF-a inhibitors versus those not treated was associated with a reduced mortality (hazard ratio for death was 0.65 (95% CI 0.46, 0.93)).…”
Section: Discussionmentioning
confidence: 99%
“…37 Systemic therapy has an effect on cardiocascular risk in both rheumatoid arthritis and psoriasis, both with systemic biological therapy and methotrexate. 38,39 In psoriasis, methotrexate downregulates the expression of the membranebound isoforms of ICAM-1, VCAM-1 and E-selectin in the skin. 21 Furthermore, the therapy decreases the soluble form of E-selectin in serum from patients with the autoimmune skin disease bullous pemphigoid.…”
Section: T Cells and Langerhans Cells Of The Inflammatory Infiltratementioning
confidence: 99%
“…Los medicamentos inhibidores del factor de necrosis tumoral (anti-TNF) se recomiendan para el tratamiento de artritis reumatoide grave activa, después de que una adecuada utilización de antirreumáticos modificadores de la enfermedad ha fallado, en espondilitis anquilosante, artritis reumatoide juvenil y artritis psoriásica resistente a los fármacos convencionales, y para el manejo de la enfermedad de Crohn de moderada a grave, en pacientes que responden en forma inadecuada a los tratamientos clásicos (10)(11)(12)(13).…”
Section: Perfil De Utilización Anti-tnfunclassified